Do Expert Surveys Produce Consistent Estimates of Party Stances on European Integration? Comparing Expert Surveys in the Difficult Case of Central and Eastern Europe - Whitefield, S; Vachudova, M; Steenbergen, M; Rohrschneider, R (Elsevier, 2006)
Expert surveys have been subject to a number of criticisms concerning their ability to produce accurate estimates of party positions. Such criticisms have particular prima facie credibility in new post-Communist democracies of Central and Eastern Europe, where party development is regarded as weak. This paper compares data from two expert surveys independently conducted between 2002 and 2004. We find, contrary to expectations, that there is a remarkable overlap in positions assigned to parties. This suggests the usefulness of expert surveys even in the ‘most difficult’ case of post-Communist party systems. It also suggests that parties in these countries have developed effective means of communicating their positions on major issues. Additional Co-Authors: Gary Marks, Matthew P. Loveless and Liesbet Hooghe